Ketogenic Diet-Induced Weight Loss is Associated with an Increase in Vitamin D Levels in Obese Adults - Maria Perticone; Raffaele Maio; Angela Sciacqua; Edoardo Suraci; Angelina Pinto; Roberta Pujia; Roberta Zito; Simona Gigliotti; Giorgio Sesti; Francesco Perticone (Molecules, 2019)
Vitamin D is an important micronutrient involved in several processes. Evidence has shown a strong association between hypovitaminosis D and cardio-metabolic diseases, including obesity. A ketogenic diet has proven to be very effective for weight loss, especially in reducing fat mass while preserving fat-free mass. The aim of this study was to investigate the effect of a ketogenic diet-induced weight loss on vitamin D status in a population of obese adults. We enrolled 56 obese outpatients, prescribed with either traditional standard hypocaloric Mediterranean diet (SHMD) or very low-calorie ketogenic diet (VLCKD). Serum 25(OH)D concentrations were measured by chemiluminescence. The mean value of serum 25-hydroxyvitamin D (25(OH)D) concentrations in the whole population at baseline was 17.8 ± 5.6 ng/mL, without differences between groups. After 12 months of dietetic treatment, in VLCKD patients serum 25(OH)D concentrations increased from 18.4 ± 5.9 to 29.3 ± 6.8 ng/mL (p < 0.0001), vs 17.5 ± 6.1 to 21.3 ± 7.6 ng/mL (p = 0.067) in the SHMD group (for each kilogram of weight loss, 25(OH)D concentration increased 0.39 and 0.13 ng/mL in the VLCKD and in the SHMD groups, respectively). In the VLCKD group, the increase in serum 25(OH)D concentrations was strongly associated with body mass index, waist circumference, and fatty mass variation. In a multiple regression analysis, fatty mass was the strongest independent predictor of serum 25(OH)D concentration, explaining 15.6%, 3.3%, and 9.4% of its variation in the whole population, in SHMD, and VLCKD groups, respectively. We also observed a greater reduction of inflammation (evaluated by high-sensitivity C reactive protein (hsCRP) values) and a greater improvement in glucose homeostasis, confirmed by a reduction of HOMA values, in the VLCKD versus the SHMD group. Taken together, all these data suggest that a dietetic regimen, which implies a great reduction of fat mass, can improve vitamin D status in the obese.